2020
DOI: 10.1088/1757-899x/771/1/012059
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the compressive strength of hair fiber reinforced concrete using central composite design

Abstract: In society today, improper waste disposal brings about numerous problems. One of the most common residual wastes found in the municipal solid waste is human hair. This waste, which is evidently continuing to accumulate in disposal streams poses a threat if not disposed properly. Several studies have been done in the search for possibilities of incorporating hair to construction materials. In this study, the compressive strength of Hair Fiber Reinforced Concrete (HFRC) was studied aiming to find the combination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Fiber is frequently portrayed by a helpful parameter; the angle proportion which is the proportion of its length to the distance across. The use of fibers in concretes has well known advantages, as it helps in controlling the cracking, it reduces the porousness of concrete, it produces more impact resistance, and it also increases strength, ductility, shatter, abrasion resistance and delays cracking [52][53][54][55][56][57][58][59][60]. On the other hand, human hair presents properties such as unique chemical composition, high tensile strength, and high elasticity, which make it a useful material to be contained in concrete.…”
Section: Use Of Hair Fibers In Concretementioning
confidence: 99%
“…Fiber is frequently portrayed by a helpful parameter; the angle proportion which is the proportion of its length to the distance across. The use of fibers in concretes has well known advantages, as it helps in controlling the cracking, it reduces the porousness of concrete, it produces more impact resistance, and it also increases strength, ductility, shatter, abrasion resistance and delays cracking [52][53][54][55][56][57][58][59][60]. On the other hand, human hair presents properties such as unique chemical composition, high tensile strength, and high elasticity, which make it a useful material to be contained in concrete.…”
Section: Use Of Hair Fibers In Concretementioning
confidence: 99%
“…Response surface methodology (RSM) was used to find the best suitable concentration of hair fiber for concrete reinforcement. It was observed that with 3.2% hair by volume of concrete and a hair strand length of 0.752 inches, an optimal concrete strength of 38.15 MPa can be achieved [13]. It was found that bending stress of 5.68 MPa was produced at 2% of hair fiber addition [14], [15].…”
Section: Introductionmentioning
confidence: 99%
“…Petrounias P. et al [17] studied the preparation of concrete and evaluated its mechanical properties using hair fibers as ditives. Furthermore, studies [18][19][20] have demonstrated the positive effects of incorporating various fiber materials such as polypropylene and glass into road subgrade mixtures in different proportions. These studies conducted comparative analyses between mixtures with fibers and those without fibers, assessing mechanical and physical properties such as uniaxial compressive strength and flowability.…”
Section: Introductionmentioning
confidence: 99%